Effects of an environmentally relevant PCB-mixture on immune function, clinical chemistry, and thyroid hormone levels in adult female B6C3F1 mice. Issue 7 (3rd April 2021) - Fair, Patricia A.; Peden-Adams, Margie M.; Mollenhauer, Meagan A.M.; Bossart, Gregory D.; Keil, Deborah E.; White, Natasha D.
ABSTRACT: Polychlorinated biphenyls (PCBs) have been assessed for immunotoxicity; however, humans and wildlife are exposed to multiple PCBs environmentally. Therefore, the aim of this study was to examine the effects of a complex 37 PCB congener mixture identified in blubber specific to dolphins residing in the estuarine waters of Charleston, South Carolina. Immunotoxicity was determined in adult female B6 C3 F1 mice by assessing lymphocyte proliferation, splenic and thymic immunophenotypes, and IgM production. Mice were exposed via oral gavage to the PCB-mixture (0, 1.8, 3.6, 7.1, or 14.3 mg/kg/day) for 28 days to yield a targeted total administered dose (TAD) 0, 50, 100, 200, or 400 mg/kg. Significant increased liver weight occurred at the highest treatment. IgM production was suppressed compared to control for all treatments. Numbers of thymic CD4+/CD8+, CD4-/CD8-, and CD4+/CD8- cells were not altered, but numbers of thymic CD4-/CD8+ cells were significantly increased in the highest treatment. Lymphocyte proliferation was not markedly affected by any treatment. The numbers of splenic CD4/CD8 T-cells or MHCII+ cells were not significantly changed. Humoral immunity using the plaque-forming cell assay for determining the specific IgM antibody-forming cell response appeared to be the most sensitive endpoint affected. As the lowest concentration tested resulted in decreased IgM production and total and free thyroxine (T4 ) serum levels a NOAEL was not identified. The calculated ED50 for suppression of IgM production was 2.4 mg/kg/day.